Healthcare alarm system - Ong, Yuan Hong (2016)
An ageing population will have a significant impact on Singapore in the next 50 years, where the number of citizens aged 65 years is projected to more than double the current number. This means the ratio will increase from 1 senior aged above 65 in 9, to 1 in 5. Ageing population also translates to better healthcare needed to allow people to live longer.1 As we progress towards a more developed nation, more emphasis is placed on healthcare. Applications, such as “iHealth SG”, allow users to look for the nearest clinics. Not everyone can take care of themselves. Even as healthcare continues to evolve in this modernized society, not everyone can be admitted to hospital promptly or have someone to care for them all the time. Introducing a healthcare alarm system that can detect anomalies from the user’s body and send out notifications via a text message anytime with a network connection. This can greatly reduce the chance of senior citizens not being attended to when any anomalies occur.